Dynamic changes in cardiac morphology, function, and diffuse myocardial fibrosis duration of diabetes in type 1 and type 2 diabetic mice models using 7.0 T CMR and echocardiography - Zhang, H.; Shi, C.; Liu, D.; Gao, H.; Zhao, Q.; Zhang, N.; Yang, L.; Wang, Y.; Du, Y.; Li, Q.; Bo, K.; Zhuang, B.; et al. (Frontiers Media, 2023)
Background: Diabetes mellitus (DM) is associated with an increased risk of cardiovascular disease (CVD). Hence, early detection of cardiac changes by imaging is crucial to reducing cardiovascular complications.